Influence of dielectric material near tunnel junction on analog/RF and linearity figure of merits in hetero dielectric (HG) TFET: A detailed study. Issue 1 (25th September 2021) - Saha, Rajesh; Sahu, Chitrakant
Abstract: In this work, the effect of dielectric material near the source region on analog/RF and linearity figure of merits in hetero gate TFET (HG‐TFET) are investigated through Technology Computer Aided Design device simulator. The various dielectric materials considered in this study are SiO2, Al2 O3, and HfO2 . The several RF/analog metrics studied in this work are transconductance (gm ), output conductance (gd ), gain (gm /gd ), gate capacitance, cut‐off frequency, and gain frequency product. Furthermore, the various linearity parameters discussed are higher order derivative of gm (gm2 and gm3 ), voltage intercept points (VIP2 and VIP3), 3rd‐order input intercept power, and 3rd‐order intermodulation power for different high‐k dielectric near the source region in HG‐TFET. Results reveal that RF/analog performance is improved, whereas, the linearity characteristic is suppressed in HG‐TFET using HfO2 as the gate dielectric near the source.